2017
DOI: 10.17559/tv-20160304113800
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tailings and cement type on durability properties of self-compacting concrete

Abstract: Preliminary communicationIn order to examine the differences in chemical composition and the possibility of using mine tailings in mortar and concrete production, samples were taken from the landfill and directly from the production. Tailings test results showed no pozzolanic activity and that its application in concrete can be only a partial replacement of aggregate. This paper presents the possibility of using tailings in self-compacting concrete made with Portland cement and sulphate resistant cement. Concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…A UCS of 58 MPa was reached with a w/c of 0.7. Other researchers [26,48,49] confirmed that the use of IOT may cause a decrease in concrete workability and an increase Also, the metric analysis of the literature based on Scopus data shows multiple works dealing with the recycling of various mine waste types in the concrete industry that are plotted according to the year of publication in Figure 5, and it shows a higher number of publications in terms of all of mine waste types this last decade. In addition, the recycling of IOT in concrete has been extensively studied, according to the number of publications, while publications dealing with the recycling of phosphate mine waste in concrete are less common.…”
Section: Iron Ore Tailings (Iot)mentioning
confidence: 84%
See 3 more Smart Citations
“…A UCS of 58 MPa was reached with a w/c of 0.7. Other researchers [26,48,49] confirmed that the use of IOT may cause a decrease in concrete workability and an increase Also, the metric analysis of the literature based on Scopus data shows multiple works dealing with the recycling of various mine waste types in the concrete industry that are plotted according to the year of publication in Figure 5, and it shows a higher number of publications in terms of all of mine waste types this last decade. In addition, the recycling of IOT in concrete has been extensively studied, according to the number of publications, while publications dealing with the recycling of phosphate mine waste in concrete are less common.…”
Section: Iron Ore Tailings (Iot)mentioning
confidence: 84%
“…A UCS of 58 MPa was reached with a w/c of 0.7. Other researchers [26,48,49] confirmed that the use of IOT may cause a decrease in concrete workability and an increase in w/c ratio due to the high water absorption of IOT [50], which is related to the particles' surface texture.…”
Section: Iron Ore Tailings (Iot)mentioning
confidence: 94%
See 2 more Smart Citations
“…There is a small number of studies about the use of wood as a replacement for fine aggregate or mineral additive [23][24]. Numerous studies have shown that waste powders with low pozzolanic activity can be successfully used as mineral admixtures for production of selfcompacting concrete [25][26][27][28][29]. Elinwa et al [24] studied the impact of sawdust ash on the properties of SCC in fresh stated and concluded that adding the sawdust ash reduces workability of concrete, but that the increase of the amount of superplasticizer can achieve a satisfactory workability.…”
Section: Introductionmentioning
confidence: 99%